Photochemically Triggered Alkylthiol Reactions on Highly Ordered Pyrolytic Graphite - COLAVITA, PAULA; GIORDANI, SILVIA (My University, 2011)
The surface of highly ordered pyrolytic graphite (HOPG) has been modified using a new photochemically induced grafting reaction. Thiols have been revealed to behave as privileged substrates for this efficient grafting process. The reaction occurs under extremely mild conditions with visible light and at room temperature. The formation of molecular layers on the graphitic surface has been probed by X-ray photoelectron spectroscopy, cyclic voltammetry, and infrared reflectance absorption spectroscopy. The reaction was investigated in the presence of thiols bearing different terminal groups (−COOH, −OH, −CH(NHCOCH3)COOH, −COOCH2CH3) and in different solvent solutions (DMF, EtOH, CH3CN). Carboxyl and hydroxyl groups as well as the use of acetonitrile as a solvent were found to facilitate the reaction. Our results suggest that the reaction mechanism proceeds via photoinduced electron transfer from the HOPG into the liquid to form highly reactive alkyl radicals able to graft the surface. This type of reactivity of a graphite substrate may be important for general modification strategies of nanotubes and graphene and for new applications of carbon-based materials in photocatalysis.
PUBLISHED
Keywords: Photochemical; HOPG; Graphite; Functionalization; Thiols; Mercaptans; Organothiols; Photoinduced; Photoreduction; Nanoscience & Materials